1993
DOI: 10.14430/arctic1315
|View full text |Cite
|
Sign up to set email alerts
|

Breeding Biology of Red-throated Loons in the Canadian Beaufort Sea Region

Abstract: ABSTRACT. The breeding biology of the red-throated loon in the Canadian Beaufort Sea region was investigated from 1985 to 1989. Five study plots were established with a total area of 276 k m 2 and over 200 pairs of loons on territory each breeding season. Loon densities ranged from 0.6 pairs*km-2 on the Yukon coast to 1.8 paiwkm-2 at Toker Point on the Tuktoyaktuk Peninsula. An average of 73% of the pairs on territory nested each year. Productivity averaged 0.63 youngmesting pair-'. The median date of egg layi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…The increasing tendency to abandon a tarn after a breeding failure is in accordance with previous results for Red-throated Divers in e.g. Canada and on Shetland (Gomersall 1986, Dickson 1993.…”
Section: Nest Site Fidelity and Changes Of Nest Sites And Breeding Tarns Between Breeding Seasonssupporting
confidence: 92%
See 1 more Smart Citation
“…The increasing tendency to abandon a tarn after a breeding failure is in accordance with previous results for Red-throated Divers in e.g. Canada and on Shetland (Gomersall 1986, Dickson 1993.…”
Section: Nest Site Fidelity and Changes Of Nest Sites And Breeding Tarns Between Breeding Seasonssupporting
confidence: 92%
“…I flera fall var häckningstjärnen övergiven bara under något-några enstaka år, varefter den åter nyttjades av ett häckande smålomspar. Också på Shetlandsöarna och i tundraområden i Kanada har man funnit att smålommarna är benägna att överge en häckningstjärn efter ett misslyckande (Gomersall 1986, Dickson 1993.…”
Section: Häckningsframgång Med Hänsyn Till Boets Storlek Och Placeringunclassified
“…In northwest Canada, the glaucous gull was the only predator species seen taking the young of redthroated loons (Dickson, 1993). Predation on red-throated loon chicks was apparently limited to those less than 10 days old, and the greatest loss of young occurred in a year when there was a significantly large number of glaucous gulls in the study area (Dickson, 1993).…”
Section: Survival Of Youngmentioning
confidence: 90%
“…Strong (1990) concluded that habitat conditions for breeding common loons (Gavia immer) are reflected most accurately by reproductive output, and that the best measurement of reproduction may be a count of prefledged chicks 7 -10 weeks old. Dickson (1993) similarly indicated for redthroated loons (Gavia stellata) that reproductive success, as measured by young that survive to fledging, was a good indication of local habitat conditions. Andres (1993) suggested that local foraging behavior of Pacific loons should be determined before they are used as an indicator of freshwater habitat conditions.…”
Section: Introductionmentioning
confidence: 95%
“…2; Beardsell et al 2016). All these species can reuse the approximate nest location from year to year (Dickson 1993, Gauthier et al 2015, Beardsell et al 2016). For each species, we used a cluster analysis to define a number of nesting zones that had a species‐specific diameter and that can be used repeatedly (annually) for nesting (Supporting information for the detailed calculation of nesting zones).…”
Section: Methodsmentioning
confidence: 99%